Educational management and quality of technological higher education in state institutions of Metropolitan Lima - Kevans Espinoza, Martha Marlene (2020)
The research determines the relationship between educational management and quality of education of the state institutes of Higher Technological Education of metropolitan Lima. We worked with two samples: 346 students and 211 teachers. The instrument was the questionnaire adapted from the Matrix of Standards for the Accreditation of Study Programs (SINEACE). The study is descriptive level and used two research designs: correlational and comparative descriptive. To estimate parameters and analyze the hypotheses presented, the Rho Spearman correlation coefficient was applied and to perform the comparisons of the samples, the Mann-Whitney U test. The results show that there is a significant relationship between educational management and quality of education. Likewise, there are significant differences between the dimensions of educational management and the dimensions of the quality of education, obtaining lower average scores for teachers, compared to students.